Meningkatkan Pembentukan Karakter di Pesantren: Mengatasi Perbedaan Pemahaman Fiqh dan Aqidah di Kalangan Santri Baru - Rizal, Mohammad Syifaur Rizal; Tsamar Nur Aini (LPTNU Sumenep, 2024)
This study aims to analyze the implementation of an inclusive and moderate approach in shaping the character of new students at the Nurul Jadid Islamic Boarding School, especially in dealing with differences in understanding of Fiqh and Aqidah. Through a qualitative case study, data were obtained from interviews with the boarding school manager, teachers, and students and direct observation in the field. The study results indicate that this approach effectively creates a harmonious and tolerant learning atmosphere where students can understand differences in views without sacrificing the principles of Islamic brotherhood. In addition, the Furudhul Ainiyah Program, implemented specifically for new students, has been proven to help them understand basic religious obligations with an applicable and interactive approach. Mentoring by senior students and foster parents also plays an important role in accelerating the adaptation of new students, both in academic, social, and emotional aspects. This study concludes that an inclusive and moderate approach, with a strong basic religious education program and social mentoring, contributes greatly to the formation of the character of students in Islamic boarding schools